Ionospheric conductivity from the ionograms recorded at Phu Thuy, Hanoi - Hồng, Phạm Thị Thu; Mazaudier Christine, Amory-; Minh, Lê Huy (Vietnam Journal of Earth Sciences, 2013)
This is the first study result about the structure of the ionospheric conductivity at the northern tropical crest of ionization in Vietnam. This paper presents briefly the theory of the ionospheric conductivity and shows the Pedersen and Hall conductivity profiles derived from ionograms recorded at Phu Thuy, Hanoi during the 1996 - 2004 period and the MISIS90 atmospheric model. We analyzed  the diurnal, seasonal and sunspot cycle variations of ionospheric conductivity during magnetically quiet days during the period of interest.The profiles of the Hall and Pedersen ionospheric conductivities showed a maximum at 12.00 LT; Hall conductivity reached to maximum at an altitude of around 107.3±0.5 Km, meanwhile the profiles of the ionospheric Pedersen conductivity  reached to maximum at altitude of around 127.1±0.8 Km. Maximum amplitude of Hall conductivity was greater than the one of Pedersen conductivity. Both conductivities varied clearly with the season and  the amplitude of these maximums was greater in summer than in other seasons. The Hall and Pedersen ionospheric conductivities varied also on the time depending on the sunspot number.